Simulasi Sistem Kendali PID Lingkungan Kelembaban Tanaman Hortikultura pada Green House untuk Inovasi Pangan Lokal - Alimuddin Alimuddin; Adika Surya Adika Surya (Leuit (Journal of Local Food Security), 2020)
The research is aims to create a humidity control system simulation horticultural palnts in the greenhouse. The controls used are PI and PID. This control system is simulated using the Simulink Matlab software. The constant values of P, I, and D are obtained using Matlab's  application, namely PID Tuner. PI control uses a proportional constant value of 3.7174 and an integral of 0.12173. Meanwhile, PID control uses a proportional constant value of 0.61842, an integral of 0.05412, and a derivative of 0.15797. PI control system response time analysis has a rise time of 0.769 seconds, a settling time of 8.7 seconds, and an overshoot of 1.57%. Meanwhile, the response time for the PID control system has a rise time of 6.51 seconds, a settling time of 11.3 seconds, and an overshoot time of 0.103%. The PI control system has the fastest response time up and setting time but has a greater overshoot compared to the PID control system.